EFFORTS TO DEVELOP FINE MOTOR ASPECTS IN COORDINATING EYES AND HANDS TO MAKE COMPLEX MOVEMENT USING EXPLICIT INSTRUCTION MODEL AND ASSIGNMENT METHOD - Asmar, Mahlan; Wahyu, Wahyu (Journal of K6, Education and Management, 2018)
This research is aimed to discover the teacher activities, the children activities, and the results of fine motor aspect development in coordinating the eyes and the hands using combination of explicit instruction model and assignment method. This research was classroom action research qualitative approach and conducted on a group of children at Budi Mulia Kindergarten of Kandangan of South Hulu Sungai District within 2 cycles, the cycle I consisted of 2 meetings and Cycle II consisted of 2 meetings. Each meeting consisted of 4 stages planning, implementation, observation, and reflection. The research results showed that teacher and children activities increased, and the development of children fine motor aspect were successfully developing whether individually or classically.